Stent-assisted coiling of large common femoral artery pseudoaneurysm following coronary artery catheterization: an uncommon and novel approach - Mahjoob Mohammad Parsa; Khaheshi Isa; Naderian Mohammadreza (Sciendo, 2017)
The femoral artery pseudoaneurysm is a disturbing groin complication associated with the femoral arterial access site used for invasive cardiovascular interventions. We present a 39 year old man who developed a huge right common femoral artery pseudoaneurysm, following diagnostic coronary artery catheterization, which was successfully managed with stent-assisted coiling, an emerging and narrative option in invasive percutaneous approaches to femoral artery pseudoaneurysm.